2019
DOI: 10.1136/gutjnl-2019-318440
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of anti-TNF therapy has not yielded expected declines in hospitalisation and intestinal resection rates in inflammatory bowel diseases: a population-based interrupted time series study

Abstract: ObjectivesTo better understand the real-world impact of biologic therapy in persons with Crohn’s disease (CD) and ulcerative colitis (UC), we evaluated the effect of marketplace introduction of infliximab on the population rates of hospitalisations and surgeries and public payer drug costs.DesignWe used health administrative data to study adult persons with CD and UC living in Ontario, Canada between 1995 and 2012. We used an interrupted time series design with segmented regression analysis to evaluate the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
131
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(138 citation statements)
references
References 39 publications
4
131
1
2
Order By: Relevance
“…Of those six, five patients had been recently started on IFX, and therefore, we suggest that their need for surgery was most likely as a result of the severity of underlying disease rather than loss of response to IFX. We know from previous studies that a relatively high percentage of IBD patient's will require surgery despite treatment with biologic therapy …”
Section: Discussionmentioning
confidence: 99%
“…Of those six, five patients had been recently started on IFX, and therefore, we suggest that their need for surgery was most likely as a result of the severity of underlying disease rather than loss of response to IFX. We know from previous studies that a relatively high percentage of IBD patient's will require surgery despite treatment with biologic therapy …”
Section: Discussionmentioning
confidence: 99%
“…For example, anti-TNF agents rapidly suppress inflammation and induce remission but did not change the long-term course in certain subsets of pediatric CD patients [108]. Murthy et al showed that anti-TNF therapy did not reduce the frequency of hospitalization and surgical treatments in CD patients [109]. Therefore, more physiological approaches to induce and sustain remissions with limited toxicity and high cost-effectiveness are needed.…”
Section: Reversing Dysbiosis As a Nontoxic Treatment Of Ibdmentioning
confidence: 99%
“…6,7 IBD is a heterogeneous group of diseases with highly variable disease phenotypes and clinical courses, and patients will likely have different responses to each biologic class depending on their specific disease subtype. Despite widespread clinical adoption of anti-TNF therapy, nearly half of the CD patients placed on biologics do not experience clinical response, resulting in dramatic increase in healthcare costs without significant improvement in outcomes 8,9 The annual costs of IBD treatment have increased by 30% within the last 5 years, 9 and IBD-related hospitalizations quadrupled from 1998 to 2015. 10,11 Over the past decade, advances in disease pathogenesis from genomics, proteomics, and microbial and host metabolomic studies, also known as "multi-omics" approaches have identified key factors responsible for ongoing mucosal inflammation in IBD.…”
Section: Introductionmentioning
confidence: 99%